1995
DOI: 10.1111/j.1472-8206.1995.tb00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol therapy in experimental heart failure in rabbits improves cardiac response to catecholamines without beta‐adrenoceptor up‐regulation

Abstract: Beta-blockade has been shown to improve cardiac response to catecholamines in heart failure but cellular mechanisms of the improvement are unknown. The effect on left ventricular function of a 14 day propranolol treatment was studied in seven treated and eight non-treated rabbits with experimental heart failure. All animals were subjected to a volume (aortic insufficiency) plus pressure (aortic constriction) overload and were instrumented with a left ventricular catheter and ultrasonic crystals measuring anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The role of ␤-blockade in the management of AR has been explored by other investigators in animal models (1,19,21,(23)(24)(25)(26)(27) (Table 4). These studies have suggested that adrenergic blockade may be beneficial in animal models of acute AR, although none of them evaluated the long-term effects in a chronic AR model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ␤-blockade in the management of AR has been explored by other investigators in animal models (1,19,21,(23)(24)(25)(26)(27) (Table 4). These studies have suggested that adrenergic blockade may be beneficial in animal models of acute AR, although none of them evaluated the long-term effects in a chronic AR model.…”
Section: Discussionmentioning
confidence: 99%
“…␤-Blockers may have acted in the same way in our animals with severe chronic AR but preserved LV ejection fraction. Indeed, we observed that Met improved the ratio of gene expression of the ␤ 1 -and ␤ 2 -adrenergic receptors, which (19) Rat AR (chronic) Met (25 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 ) for 6 mo Improvement of LVEF, decrease in LVH, increase in ␤1-AR expression Suzuki et al (21) Rabbit AR (acute) Intravenous propranolol for 7 days Prevention of ␤-AR downregulation Wright et al (23) Rabbit AR (8 wk) Bradycardial pacing Improvement of myocardial capillary density and cardiac work per minute in AR Xiong et al (24) Rabbit AR (acute, 14 days) Propranolol Improvement of fractional shortening; no effect on ␤-AR; possible protection against toxic effects of catecholamines Yamazaki et al (25) Rat AR (8 wk) No treatment Increase in synthesis of ␤-AR from week 1 to week 4 and return to baseline by week 8 Yoshikawa et al (26) Rabbit AR (acute, 7 days) Alacepril (ACEI) for 7 days Prevention of acute decrease in myocardial ␤-AR density and NE content LVEF, LV ejection fraction; LVH, LV hypertrophy; ACEI, angiotensin-converting enzyme inhibitor; ␤-AR, ␤-adrenergic receptor; NE, norepinephrine. …”
Section: Discussionmentioning
confidence: 99%
“…20 Significant abnormalities of the adrenergic system have also been identified in humans and animals submitted to chronic volume overload. [2][3][4][5][6][7][8][9][10][11][12]21,22 Others have reported significant decreases in ␤-adrenoreceptor density in the LV of patients with chronic volume overload compared with pressure-overload and normal controls. 23 In subjects with clinical heart failure from severe AR, intense adrenergic activity is present, as in other causes of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…1 Significant alterations of the adrenergic system and adrenergic receptors have been reported in animal models of chronic volume overload. [3][4][5][6][7][8][9][10][11][12] Despite these interesting findings, the hypothesis that ␤-adrenergic blocking agents might be effective to protect the volume-overloaded LV has not been adequately tested. A few studies have suggested that a short-term treatment with ␤-blockers might be beneficial in volume overload.…”
mentioning
confidence: 99%
See 1 more Smart Citation